Optical coherence tomography: an experimental validation for vascular imaging of saphenous vein bypass grafts. (24th February 2016) - Wilson, Rebekah; Aung, Hnin; Ju, Xiangyang; Paterson, Craig; Sayer, Robin; McIntyre, Alan; Going, James; Irvine, Richard; Berry, Colin
Abstract: Purpose. Optical coherence tomography (OCT) is a novel light-based intravascular imaging method with potential utility for quantifying vascular disease and the effect of therapy. OCT has been used to image vein grafts and neointima in clinical research studies but validity of OCT for vein graft imaging is limited by depth of field and tissue penetration. Experiments were carried out to validate the in-house developed new software (Medipass-iScan) and OCT vendor software comparing with a gold standard, photomicroscopy. Methods. Seven synthetic phantom tubes with varying inner diameters and eight saphenous veins were imaged with OCT. Imaging was performed five times on each phantom/vessel and sections of each were measured by photomicroscopy. OCT images were analyzed by iScan to measure the inner diameters and then compared with corresponding microscopy sections. Results. A Bland–Altman plot of differences between photomicroscopy and OCT measurements of phantoms, demonstrated evidence of limited bias (104 μ m) and 95% limits of agreement, −100 and 308 μ m. The mean variation of iScan OCT measurements from microscopy was 3.02% and that of the OCT vendor software 3.03%. Conclusions. OCT has high measurement accuracy of lumen diameter. iScan measurements of saphenous veins imaged by OCT had similar accuracy to vendor software, supporting its validity. Potentially, OCT may be used to measure saphenous vein dimensions ex vivo.